Perancangan Sistem Pendukung Keputusan Pemilihan Mata Pelajaran Menggunakan Metode SAW di MAN 1 Pasaman - Dinda Putri Dewi Harefa; Liza Efriyanti; Supriadi Supriadi; Riri Okra (Lembaga Yasin AlSys, 2026)
Although the application of decision support systems in education has been widely studied, research that specifically examines the design of decision-making systems for selecting elective subjects under the Kurikulum Merdeka is still limited. This study aimed to design and test a decision-making system for determining elective subjects for students using the Simple Additive Weighting (SAW) method at MAN 1 Pasaman. The study employed a Research and Development (R&D) approach with the ADDIE development model. The participants consisted of 30 Grade X students and 2 teachers selected through purposive sampling. Data were collected through interviews, observations, and questionnaires, and were analyzed using both qualitative and quantitative approaches. The results showed that the developed system had a high level of validity, with an average Aiken’s V value of 0.963, very high practicality, and high effectiveness with an n-gain value of 0.72. These findings indicate that the system is capable of providing objective and effective recommendations for subject selection. The study concludes that the SAW-based decision-making system contributes to supporting the implementation of the Kurikulum Merdeka through the use of data-driven decision-making at MAN 1 Pasaman.